2005
DOI: 10.1088/0266-5611/21/6/017
|View full text |Cite
|
Sign up to set email alerts
|

The multiple-sets split feasibility problem and its applications for inverse problems

Abstract: The multiple-sets split feasibility problem requires to find a point closest to a family of closed convex sets in one space such that its image under a linear transformation will be closest to another family of closed convex sets in the image space. It can be a model for many * Accepted for publication in the journal Inverse Problems. 1 inverse problems where constraints are imposed on the solutions in the domain of a linear operator as well as in the operator's range. It generalizes the convex feasibility pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
438
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 649 publications
(444 citation statements)
references
References 35 publications
3
438
0
3
Order By: Relevance
“…For more results on split feasibility problems, the readers refer to [3,4,6,9,29,34,35]. Now, by Theorem 3.1 and Theorem 4.2, we give the following results on split feasibility problems in Banach spaces: Theorem 5.1.…”
Section: Applicationsmentioning
confidence: 96%
See 1 more Smart Citation
“…For more results on split feasibility problems, the readers refer to [3,4,6,9,29,34,35]. Now, by Theorem 3.1 and Theorem 4.2, we give the following results on split feasibility problems in Banach spaces: Theorem 5.1.…”
Section: Applicationsmentioning
confidence: 96%
“…Recently, split feasibility problems [3,4,6,9,29,34,35], split variational inequality problems [10,21] and split equilibrium problems [2,17,31] have been investigated by many authors. However, most of the results on these kinds of these problems are investigated only in Hilbert spaces, only a few works are considered in Banach spaces.…”
Section: Introductionmentioning
confidence: 99%
“…Recall that the multiple-set split feasibility problem (MSSFP, for short), which was first introduced by Censor et al [5]: 1) where N, M ≥ 1 are integers,…”
Section: Applicationsmentioning
confidence: 99%
“…To solve the MSSFP (4.1), Censor et al [5] first proposed a gradient projection algorithm. However, this iterative algorithm could not reduce to the CQ iterative algorithm [3] for solving the SFP (4.2).…”
Section: Applicationsmentioning
confidence: 99%
“…It has been found that the split feasibility problem can also be used in various disciplines such as image restoration, computer tomograph and radiation therapy treatment planning [4,5,7].…”
Section: Introductionmentioning
confidence: 99%